Diffusion and adoption of Integrated Striga Management (ISM) technologies among smallholder maize farmers in rural northern Nigeria. (February 2019) - Baiyegunhi, L.J.S.; Hassan, M.B.; Danso-Abbeam, G.; Ortmann, G.F.
Abstract: This study estimated the actual and potential adoption rates of Integrated Striga Management (ISM) technologies, among smallholder maize farmers in rural northern Nigeria, using the treatment effect framework. The results revealed a significant overall adoption rate of 55% of the targeted population while 83.5% of the farmers were exposed to the ISM practices. With such an incomplete diffusion of the ISM technologies, the study estimated potential adoption rate to be 68.2%, while the actual adoption (JEA) rate was estimated to be 58.3% resulting in an adoption gap of 9.9% due to incomplete diffusion/exposure. In addition, diffusion and adoption of ISM technologies were found to be influenced by factors such as famer's years of farming experience, total farm size under maize cultivation, cooperative society's membership, attendance of farm workshop/seminars, on-farm trials and field days among others. Policy implications for increase productivity and food security through ISM technology diffusion and adoption were discussed. Highlights: Actual and potential adoption rates ISM technologies were estimated by treatment effect model. Adoption rate of the targeted population is 55%, while 83.5% of the farmers were exposed to ISM technologies. Estimated potential adoption rate was 68.2%, while the actual adoption (JEA) rate was 58.3%. There was an adoption gap of 9.9% due to incomplete diffusion/exposure. Adoption gap can be close by improvement in both diffusion and adoption process.